Is Systemic (Interstitial Fluid) Acidosis an Initial Event in the Etiopathogenesis of Dental Caries? A Hypothesis - Sandhya Tamgadge; Avinash Tamgadge (Wolters Kluwer Medknow Publications, 2018)
Introduction: Dental caries is a microbial disease which affects retentive areas of the teeth. It has shown significant increase in incidence and prevalence in modern population. Various theories have been postulated in an attempt to explain the etiopathogenesis of dental caries. Despite their popularity, there are many questions which various theories haven't been able to answer. And still there is no definite cure for dental caries. Consequently, in most cases the process can't be reversed. Therefore, to tackle this issue other risk factors involved in the etiopathogenesis need to be explored. The Hypothesis: It could be suggested that there might be additional systemic factors, e.g. systemic acidosis, in pathogenesis of dental caries, in addition to proven localized causative factors. Evaluation of the Hypothesis: Various hypotheses have been discussed, on the basis of histopathology, and various research articles. The demineralization of bone osteoporosis and tooth demineralization of dental caries have been correlated to evaluate the hypothesis. Few parameters have been added in the proven local factors of etiopathogenesis of dental caries.